Pluralizing and problematizing carbon finance. (August 2020) - Bridge, Gavin; Bulkeley, Harriet; Langley, Paul; van Veelen, Bregje
Growing emphasis on finance as key to decarbonization requires social science research that critically attends to the emergent and diverse forms taken by carbon finance. First, we pluralize research into carbon finance, building on existing work to identify four main forms: carbon markets; ecosystem services; natural capital investment; and, capital allocated to low-carbon enterprises and projects. Second, we propose that research should problematize the processes through which carbon is variously translated into financial value. Illustrated with reference to low-carbon investment in electricity generation, our agenda thereby extends from the difficulties of producing carbon-as-commodity to the uncertainties of constituting carbon-as-asset.